PENERAPAN MESIN PRODUKSI KAYU MULTI FUNGSI UNTUK MENINGKATKAN PRODUKTIVITAS UMKM MEBEL KOTA KUPANG - Nursalim Nursalim; Agusthinus S. Sampeallo; Abdul Wahid; Nixson J. Meok (KACANEGARA Jurnal Pengabdian pada Masyarakat, 2021)
The lifestyle of the people of NTT which is increasingly modern creates opportunities for furniture business such as UD furniture. Gusti Karya is more and more open. Due to the increasingly modern lifestyle of society, the lifestyle will be more consumptive, luxurious, individualistic, and instantaneous. UD. Gusti Karya is a partner of the PPPUD program located on Jalan Bajawa, Kupang City. This business has been started since 1997. However, the increasing number of days, the resulting turnover has decreased. This is due to the limited equipment they have, so the number of products they produce is very limited. This program aims to provide solutions to problems currently being faced by partners related to the problem of increasing their production. The solution offered is to implement a multi-functional wood production machine. Because according to the partner, since the business began, the partner has never renovated any equipment, let alone used a wood production machine with more modern technology. This problem then causes the production process to be very slow, causing productivity to decrease. The results of the activity evaluation show that, by implementing a multi-functional wood production machine in this PPPUD program, the partner's production process has increased according to the objectives of this program.